Financial Satisfaction of Students in Serang City: The Importance of Financial Literacy and Financial Management Behavior - Sunandi, Among; Hidayat, Desman (Universitas Pendidikan Nasional, 2023)
Financial difficulties are not always caused by the influence of income, but are also influenced by mistakes in financial management, such as not planning a financial plan, consumer living and various other problems. Especially students in the teenage age group, who still need the ability to manage their own finances to achieve financial satisfaction. Apart from that, students are also a group that has a big impact on the economy. There is a research gap which suggests that financial literacy has a significant effect on financial satisfaction and vice versa. Therefore, there is a need for mediating variables to increase financial satisfaction significantly. So, researchers want to conduct research with the aim of finding out the effect of financial literacy on financial satisfaction, by considering financial management behavior as an intervening variable. This is to find out the extent to which a person's level of financial literacy influences their financial management behavior, and whether this financial management behavior plays a role in linking financial literacy with financial satisfaction. Based on the discussion and hypothesis testing using the partial least squares (PLS) analysis method, it can be concluded that financial literacy influences the financial management behavior of female students on campuses in the Serang city area, meaning that the better the financial literacy of a person or group, the better the behavior. managing one's finances. Financial literacy does not directly influence the financial satisfaction of female students in the city of Serang. This means that as a person's level of Financial Literacy increases, their Financial Management Behavior can improve. So, it is very important to mediate Financial Management Behavior on the Financial Satisfaction of female students in the city of Serang.